ESPI Solution for Defect Detection in Crystalline Photovoltaic Cells - Yin, Ching-Chung; Wen, Tzu-Kuei (My University, 2011)
The yield of photovoltaic (PV) cells is often reduced by micro-defects in crystalline silicon substrates during fabrication. Common optical inspection for a thin crack in such a large silicon photovoltaic cell is extremely time-consuming and fails in efficiency. This study developed a method of using electronic speckle pattern interferometry (ESPI) for rapidly testing for cracks in an entire field of PV cells. Thermally induced flexural cell deformation was measured by optical configuration for ESPI measurement of out-of-plane deformations. Experimental results indicate that the speckle patterns correlating with thermal deformation of cell enable simultaneous estimation of crack size and location in both single- and poly-crystalline PV cells. This nondestructive detection method has potential applications in PV cell sorting.
Keywords: Defect detection; photovoltaic cell; electronic speckle pattern interferometry; thermal deformation